Study on the Lead pollution caused by automobile exhaust in Sylhet City (Journal of Bangladesh Academy of Sciences, 2009)
doi: 10.3329/jbas.v32i1.2450 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 117-120, 2008